Pengaruh literasi ekonomi digital terhadap kesiapan menjadi guru dimoderasi oleh gender - Mochammad Rio Aditya; Albrian Fiky Prakoso (Jurnal Riset Pendidikan Ekonomi, 2023)
This study aims to investigate the influence of digital economic literacy on teaching readiness, considering the moderating role of gender among students of the Economics Education Study Program in 2019 and 2020 at the State University of Surabaya. Digital economic literacy refers to individuals' ability to understand and utilize digital technology in an economic context. Teaching readiness involves the skills and knowledge required for effective teaching. The research data were collected from 117 students and analyzed using a quantitative approach with structural equation modeling (SEM) employing the WarpPLS approach. The results of the study indicate that digital economic literacy has a significant positive influence on teaching readiness. Higher levels of digital economic literacy correspond to greater readiness to become teachers. However, the gender variable does not moderate the influence of digital economic literacy on teaching readiness. Therefore, there is no difference between male and female students in terms of digital economic literacy and teaching readiness among students of the Economics Education Study Program in 2019 and 2020 at the State University of Surabaya.